ChemInform Abstract: [3, 3]Paracyclophanes as Planar Chiral Scaffolds for the Synthesis of New Phosphoric Acids. Issue 42 (1st October 2013) - Stemper, Jeremy; Isaac, Kevin; Duret, Veronique; Retailleau, Pascal; Voituriez, Arnaud; Betzer, Jean‐Francois; Marinetti, Angela
Abstract As a test for the newly presented phosphoric acids their application in an asymmetric transfer hydrogenation of 2‐phenylquinoline with Hantzsch‐type esters is reported.